2020
DOI: 10.3390/catal10091097
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ag and AgI-Modified ZnO as Heterogeneous Photocatalysts for Simulated Sunlight Driven Photodegradation of Metronidazole

Chao Ding,
Kun Fu,
Yishuai Pan
et al.

Abstract: Ag and AgI-modified ZnO composites (Ag/ZnO and AgI/ZnO) were synthesized in facile ways. The photocatalysts were used for the photodegradation of metronidazole (MNZ) under the irradiation of simulated sunlight. The results of experiments showed that both Ag/ZnO and AgI/ZnO had a specific molar ratio to reach the best performance. Ag/ZnO performed better in the photodegradation of MNZ than AgI/ZnO under the same conditions. The reaction rate constant of AgI/ZnO was less affected by the variation of initial conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…The SP_2 sample spectra consist of only one main peak located at 619.1 eV, as clearly identified from Figure d. We ascribed this chemical state to the presence of the AgI interlayer. Basically, it is unexpected to observe the existence of the AgI compound from the SP_2 sample because of the presence of an ITO barrier layer. In other words, halide species should not be able to directly reach the Ag layer and create an AgI structure as in the case of the SP_1 sample without an ITO barrier.…”
Section: Resultsmentioning
confidence: 79%
“…The SP_2 sample spectra consist of only one main peak located at 619.1 eV, as clearly identified from Figure d. We ascribed this chemical state to the presence of the AgI interlayer. Basically, it is unexpected to observe the existence of the AgI compound from the SP_2 sample because of the presence of an ITO barrier layer. In other words, halide species should not be able to directly reach the Ag layer and create an AgI structure as in the case of the SP_1 sample without an ITO barrier.…”
Section: Resultsmentioning
confidence: 79%
“…ZnO had a uniform nanorod shape, while the surface of Ag-ZnO contained some small nanoparticles loading onto the nanorods of ZnO. The result from SEM analysis confirmed that the silver nanoparticles were loaded over ZnO [13,21,25].…”
Section: Photocatalysts Propertiesmentioning
confidence: 75%
“…The hetero-structuralized ZnO is the highest method used for CO 2 reduction at 36%, followed by defect-engineered ZnO (32%), plasmonic metal-loaded ZnO (18%), and 14% assigned to the doped ZnO. Therefore, the development method for doping ZnO is interesting to extend the application of ZnO-based photocatalyst for the conversion of carbon dioxide [11,13,15,18,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…S1-S7). [43][44][45] Fig. 6 (a) Photocurrent study (b) time dependent photocatalytic performance comparison of performances of Ag 3.84 Sn 3 S 8 @rGO 0.25 with (c) different catalysts (d) as synthesized catalysts…”
Section: Electrochemical Impedance Spectroscopy (Eis)mentioning
confidence: 99%